2003
DOI: 10.1073/pnas.1131855100
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed resistance to microbial attack: A targeted chemical defense against marine fungi

Abstract: Pathogenic microbes can devastate populations of marine plants and animals. Yet, many sessile organisms such as seaweeds and sponges suffer remarkably low levels of microbial infection, despite lacking cell-based immune systems. Antimicrobial defenses of marine organisms are largely uncharacterized, although from a small number of studies it appears that chemical defenses may improve host resistance. In this study, we asked whether the common seaweed Lobophora variegata is chemically defended against potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
144
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(147 citation statements)
references
References 43 publications
0
144
0
3
Order By: Relevance
“…Together, bromophycolides and callophycoic acids represent the largest group of algal antifungal chemical defenses reported to date, adding to only a handful of previously identified antimicrobial chemical defenses from macroalgae (9,11,(17)(18)(19). DESI-MS imaging revealed antifungal bromophycolides both within algal tissues and among distinct patches covering only Ϸ5% of algal surfaces (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, bromophycolides and callophycoic acids represent the largest group of algal antifungal chemical defenses reported to date, adding to only a handful of previously identified antimicrobial chemical defenses from macroalgae (9,11,(17)(18)(19). DESI-MS imaging revealed antifungal bromophycolides both within algal tissues and among distinct patches covering only Ϸ5% of algal surfaces (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, such defenses were often proposed based on inhibitory effects detected in experiments, using whole organism extracts (5,7), and it is unclear whether target species actually encountered these chemicals in nature. In more ecologically realistic studies, roles of surface-associated molecules were proposed based on experiments employing surface extracts or pure compounds tested at their approximate surface concentration (6,(9)(10)(11)(12)(13). Unfortunately, current extraction-based methodologies are limited to certain classes of molecules.…”
mentioning
confidence: 99%
“…As far as we know, only 2 previous studies have demonstrated ecologically relevant effects of algal metabolites on seaweed surface colonization by microorganisms. Kubanek et al (2003) showed that one isolated compound (lobophorolide) from the brown alga Lobophora variegata inhibited growth of 2 co-occurring fungal species, Dendryphiella salina and Lindra thalassiae, at ecologically relevant concentrations. The other example is the study by Maximilien et al (1998), where it was shown that naturally occurring surface concentrations of crude extracts and purified compounds, known as halogenated furanones, of the red alga Delisea pulchra inhibited bacterial attachment in the field.…”
Section: Discussionmentioning
confidence: 99%
“…This is a crucial issue for surface active inhibitors, and the presentation of metabolites for chemical defence will ultimately depend on the nature of the structures in which these metabolites are produced and stored. However, few studies have examined the ecological roles of algal secondary metabolites in microbial antifouling at relevant surface concentrations (Kubanek et al 2003).…”
Section: Introductionmentioning
confidence: 99%